The Ventricular Assist Device team in the management of patients treated with long-term Mechanical Circulatory Support - Simone Amato; Andrea Battisti; Daniele Napolitano (Infermieristica Journal, 2024)
The number of people with heart failure is increasing rapidly worldwide. Despite preventive measures, optimal medical therapy, and cardiac transplantation, the overall morbidity and mortality of this syndrome remain high. Ventricular assist devices are well established as a treatment for heart failure and are increasingly used globally, both for destination therapy and as a bridge to cardiac transplantation. The management of these patients requires the training of a highly specialized team to ensure optimal outcomes. This article focuses on implementing a multidisciplinary team on the ventricular assist device, ensuring comprehensive care for implanted patients to mitigate potential complications early.